Evaluating Particulate Matter Reduction by Indoor Plants in a Recirculating Air System - Erich Streit; Jolan Schabauer; Azra Korjenic (Atmosphere)
Particulate matter (PM) is a major health risk, particularly in indoor environments where air quality should be optimized and pollution reduced efficiently. While technical air purification systems can be costly and impractical, indoor plants offer a sustainable alternative. Using a novel methodology, four common indoor plants were evaluated for their potential to reduce PM2.5. PM2.5 was introduced via incense in a custom-designed test chamber with air circulating at 0.3 m/s. Air quality was continuously monitored with an AirGradient Open Air device (Model O-1PST), an optical particle counter. Statistical significance was confirmed by independent t-tests and ANOVA. Calcium chloride regulated relative humidity in the chamber. The plants Epipremnum aureum, Chlorophytum comosum, Nephrolepis exaltata, and Maranta leuconeura were assessed for their PM2.5-binding capacity. Nephrolepis exaltata showed the highest reduction efficiency. Maranta leuconeura with its hemispherical leaf cells was tested for the first time and proved to trap particles within its leaf structure. It is ranked second and showed a stronger dependence on ambient PM2.5 concentrations for reduction efficiency.